Development of paediatric electrophysiology standards for Florida Children's Medical Services. (29th December 2014) - McCormack, Jorge; Seslar, Stephen; Wolff, Grace; Young, Ming; Bryant, Randall; Neghme, Rodrigo; Fishberger, Steven; Decker, Jamie A.; Sokoloski, Mary; Ho, Jason; Lawrence, David; Jenkins, Chrishonda; et al.
Abstract The Florida Children's Medical Services (CMS) has a long-standing history of ensuring that providers of multiple paediatric subspecialties abide by the highest standards. The cardiac sub-committee has written quality standard documents that participating programmes must meet or exceed. These standards oversee paediatric cardiology services including surgery, catheterisations, and outpatient services. On April, 2012, the cardiac sub-committee decided to develop similar standards in paediatric electrophysiology. A task force was created and began this process. These standards include a catalogue of required and optional equipment, as well as staff and physician credentials. We sought to establish expectations of procedural numbers by practitioner and facility. The task force surveyed the members of the Pediatric and Congenital Electrophysiology Society. Finding no consensus, the task force is committed to generate the data by requiring that the CMS participating programmes enrol and submit data to the Multicenter Pediatric and Adult Congenital EP Quality (MAP-IT™) Initiative. This manuscript details the work of the Florida CMS Paediatric Electrophysiology Task Force.